Prototype Pembelajaran Pemanfaatan Energi Baru Terbarukan Berbasis Energi Surya - Samsurizal Samsurizal; Septiannissa Azzahra; chistiono Christiono; Miftahul Fikri; Hastuti Azis; Agus Yogianto (Terang, 2021)
The use of renewable energy (EBT) is increasing to achieve the target of 23% by 2025. There needs to be a variety of preparations in welcoming the transition of fossil-based energy to renewable energy. One of them is by improving the quality of human resources that excel in developing the use of renewable energy in Indonesia. Through the Electrical Engineering PkM Team IT-PLN had the opportunity to provide counseling or education to the academic community of MA Al-Khairiyah Rancaranji. The activity is in the form of learning the installation of solar power plant components and the utilization of solar energy in the form of prototype portable plts. The learning improved students' understanding of renewable energy and was able to assemble photovoltaic system components into prototype portable plts with a capacity of 100 WP. Then the tool is tested using a lamp load of 9 watts to find out the amount of current and voltage produced. From this activity, it can be known that the students of MA Al-Khairiyah Rancaranji are very enthusiastic in knowing about renewable energy and can apply it in the surrounding environment.